Comparison on the Impact of Standardization and Adaptation on International Marketing (Global Journal of Management and Business Research, 2014)
Study of the transformation of marketing solutions in the process of internationalization of a company acknowledge that the structure of marketing strategy in international markets is an evolutionary process and companies face a particular choice: to standardize or to adapt strategic marketing solutions. Seeking for successful international performance companies do not have to adopt one extremity. The objective of the international marketing strategy is to find an ideal combination of integration and rationalization of operations and solution systems in a global market. The goal of this article is to position international companies on a linear continuum revealing their overall approach towards standardization/adaptation, study the reasons influencing international companies' tactical attitude towards it, and lastly presents the primary managerial implications of the results. Furthermore, it identifies the reasons pulling towards adaptation or standardization into significant and peripheral; and present helpful insights towards practical application.
Keywords: standardization; adaptation; international marketing